Electronic structure and conformational flexibility of d-cycloserine1. Issue 39 (21st October 2015) - Filippi, Antonello; Fraschetti, Caterina; Grandinetti, Felice; Speranza, Maurizio; Ponzi, Aurora; Decleva, Piero; Stranges, Stefano
<x xml:space="preserve">Abstract</x> The conformational flexibility effect on the valence and core electronic structures of d-cycloserine.